Management of crizotinib therapy for ALK-rearranged non-small cell lung carcinoma: An expert consensus. Issue 2 (February 2015) - Cappuzzo, Federico; Moro-Sibilot, Denis; Gautschi, Oliver; Boleti, Ekaterini; Felip, Enriqueta; Groen, Harry J.M.; Germonpré, Paul; Meldgaard, Peter; Arriola, Edurne; Steele, Nicola; Fox, Jesme; Schnell, Patrick; et al.
Highlights: Crizotinib is a standard of care for ALK-positive lung cancer. Crizotinib-associated AEs are mostly mild to moderate in severity. Appropriate monitoring and supportive therapies reduce the need for dosing modifications. Patients may have prolonged benefit from crizotinib after disease progression. Crizotinib should be continued for as long as the patient derives benefit. Abstract: Within 4 years of the discovery of anaplastic lymphoma kinase ( ALK ) rearrangements in non-small cell lung cancer (NSCLC), the ALK inhibitor crizotinib gained US and European approval for the treatment of advanced ALK -positive NSCLC. This was due to the striking response data observed with crizotinib in phase I and II trials in patients with ALK -positive NSCLC, as well as the favorable tolerability and safety profile observed. Recently published phase III data established crizotinib as a new standard of care for this NSCLC molecular subset. A consequence of such rapid approval, however, is the limited clinical experience and relative paucity of information concerning optimal therapy management. In this review, we discuss the development of crizotinib and the clinical relevance of its safety profile, examining crizotinib-associated adverse events in detail and making specific management recommendations. Crizotinib-associated adverse events were mostly mild to moderate in severity in clinical studies, and appropriate monitoring and supportive therapies are considered effective in avoiding the need for dose interruption or reduction in most cases. Therapy management of patients following disease progression on crizotinib is also discussed. Based on available clinical data, it is evident that patients may have prolonged benefit from crizotinib after Response Evaluation Criteria in Solid Tumors-defined disease progression, and crizotinib should be continued for as long as the patient derives benefit.